RANCANGAN ALAT BANTU PELEPAS WINDSHIELD PADA PESAWAT KING AIR B200 GT - Iwan Engkus Kurniawan (Jurusan Teknik Mesin Fakultas Teknik Universitas Bangka Belitung, 2022)
King Air is a type of aircraft that is supported by a dual engine, namely the PT6A-52 engine model, this engine is an engine with the latest model of its type, namely the PT6 engine. Routine maintenance of the Beechcraft King Air B200 is carried out in phase 1, phase 2, phase 3, phase 4, special inspection program, lubrication program, and continuous corrosion control inspection. Including windshield maintenance which is included in On-condition maintenance, if cracks, delamination on the glass are found, or the heater on the Windshield does not work, it must be replaced. With the weight of the windshield and the tensile load of the sealent of 47.75 kg. Then a tool is needed to help remove the Windshield. This research focuses on how to design a windshield release device using Solidworks software that is able to pull the load from the windshield and is able to hold the windshield until it is brought to the ground. The design process uses the VDI (Verein Deutscher Ingenieure) 2221 method which includes several design combinations, and then the best design is selected as desired. The design of the windshield release device uses 4 vacuum suctions to lift the windshield made of silicon and NBR with a diameter of 100 millimeters each with a suction power of one vacuum of 353.25 N and the total for 4 vacuums is 1413 N. And for the main frame, ductile iron is used. Which has a yield strength of 379 MPa and threaded using Stainless Steel 304 with a Yield Strength of 205 MPa